Sexting and Christian Teens: The Meaning of 1 Thessalonians 4:3- 5 on Self-Sanctification - Dachi, Michael Fatlin (Scriptura Indonesia, 2023)
This article discusses the phenomenon of sexting among Christian youth, highlighting the meaning of 1 Thessalonians 4:3-5 on sanctification. The primary objective of this study is to understand the impact of sexting on the lives of Christian youth and how Biblical teachings, particularly from 1 Thessalonians 4:3-5, can guide them in maintaining personal purity in the digital age. The background of this research is driven by the increasing cases of sexting among adolescents, which can lead to negative psychological and spiritual consequences. In this context, understanding Biblical teachings is highly relevant to help Christian youth realize the importance of maintaining purity in their relationships. The method employed in this study is a qualitative approach with hermeneutic analysis. The qualitative approach allows for exploring the experiences and perspectives of Christian youth related to sexting, while the hermeneutic approach is used to interpret the theological meaning of Biblical passages concerning purity in the digital world. The findings of this research are expected to provide insights for parents, pastors, and church leaders in guiding Christian youth to uphold personal purity amid the challenges of the modern world.